Penggunaan Intranet – Chat untuk Pembelajaran Bahasa Indonesia Berbalas Puisi Di Sekolah Dasar Kelas Rendah Sebagai Alternatif Pencegahan Perilaku Brutal - Ferril Irham Muzaki (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2018)
Information and Communication technology or the so-called Internet has increased the skills and skills that occur in maintaining and identity of a learner. On that basis, it is suggested to use the internet version of the local network or the so-called intranet becomes the key to changes in information and communication technology. In this case, the knowledge of information and communication technology is a major factor that encourages the creation of skills and skills in designing intranet-based learning. In this case, ability and skill are closely related to skill in designing poetry. So far, poetry is a factor that contributes to the various kinds of businesses that accompany the brutal behavior attitudes in primary school-age students are more especially low-class students. In this case, to prevent brutal behavior despite attention to the behavior and aspects that accompany the ability that accompanies the ability of learners.